Curriculum in Indonesia: An Evaluation of Implementation and Challenges in the Modern Era - Alim Billah; Muhammad Nabil Pratama; Abdurrahmansyah Abdurrahmansyah (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2026)
Despite continuous curriculum reforms, limited studies comprehensively examine the gap between policy design and classroom implementation in the modern educational context. This study aims to evaluate curriculum implementation, identify its application in schools, and analyze the challenges faced in response to technological and social changes. This research employs a descriptive qualitative approach using observation and documentation techniques. Data were obtained from educational policy documents, journal articles, and relevant reports. The analysis follows the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that curriculum implementation has generally aligned with national policy directions, particularly in strengthening competencies, character development, and student-centered learning. However, significant challenges remain, including limited teacher readiness, low digital literacy, unequal infrastructure, and disparities in educational resources across regions. These challenges collectively hinder the effective translation of curriculum policy into consistent classroom practice. Accordingly, improving human resource capacity, strengthening infrastructure, and ensuring policy consistency are critical measures that must be prioritized to achieve effective and equitable curriculum implementation across all school contexts.